Evaluation of lead time in procurement process: a case study of ministry of health & family welfare, Bangladesh - Islam, Md. Anwarul (BRAC Univeristy, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.